PENGEMBANGAN EDUKASI MASYARAKAT PENGGUNAAN PLASTIK PADA MAKANAN TERHADAP KESEHATAN DAN LINGKUNGAN DI SMA AGRIBISNIS KOTA BENGKULU - Sari, Selly Ratna; Silsia, devi silsia; syafnil, syafnil (Universitas Mataram, 2024)
The background of this of using plastic for food packaging. Materials classified as plasticizers include types such as polyvinyl chloride (PVC) and bisphenol-A (BPA), with Styrofoam also falling into the category of plastics often used for food containers despite their adverse effects. High school Agribusiness Dangau Datuk Bengkulu possesses skills in food production, maintenance, and distribution, yielding processed foods such as ice cream, ground coffee, and various other products. Vocational students market their processed products using plastic packaging. Therefore, the aim of this initiative is to impart knowledge on the use of plastic packaging in food products and its effects on health and the environment. This endeavor can enhance community abilities, particularly those of vocational students who have filled out questionnaires, numbering around 20 people. The activities are conducted through coaching methods, which involve coordination with partners, counseling, demonstrations, and promoting sustainability. Counseling materials encompass the functions of packaging for food products, types of packaging, plastic as a food product packager (including types and raw materials), the impact of using plastic packaging on health and the environment, and tips for safely utilizing plastic packaging. The educational activities proceeded smoothly, with enthusiastic participation from the attendees. The evaluation results indicated a positive and beneficial impact, ensuring that all participants acquired knowledge about the use of plastic packaging. Consequently, participants are now equipped to select appropriate packaging for the food products they produce.